2021
DOI: 10.5812/asjsm.106782
|View full text |Cite
|
Sign up to set email alerts
|

Role of Exergame Play on Cardiorespiratory Fitness and Body Composition in Overweight and Obese Children

Abstract: Background: Exergaming is an ideal vehicle for promoting regular physical activity among children who may be reluctant to participate in traditional types of exercise. Objectives: The purpose of this study was to investigate the effects of six weeks of exergaming and traditional video gaming on body composition and cardiovascular fitness variables among overweight and obese children. Methods: Thirty-one overweight and obese children (11.40 ± 0.86 years) were recruited from three primary schools in KwaZulu Nata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…One of the reasons for the fitness improvements observed in the experimental group could be that, after the children watched the videos, they made a connection between the importance and benefits of PA and actually increased their own PA. Other research has also revealed that the BB videos were effective in increasing students' self-efficacy levels in learning about PA and health (Uzunöz et al, 2017), in understanding the benefits of a healthy life (Emeljanovas et al, 2014;Tumynaite et al, 2014;Van Biljon & Longhurst, 2010), and in positively changing their attitudes towards health (Bonnema et al, 2020). In a study carried out by West and Shores (2014) to investigate the effects of the BB PA videos on the PA level of seventh-and eighth-grade students, there was an increase in the duration of student participation in moderate to vigorous activities.…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons for the fitness improvements observed in the experimental group could be that, after the children watched the videos, they made a connection between the importance and benefits of PA and actually increased their own PA. Other research has also revealed that the BB videos were effective in increasing students' self-efficacy levels in learning about PA and health (Uzunöz et al, 2017), in understanding the benefits of a healthy life (Emeljanovas et al, 2014;Tumynaite et al, 2014;Van Biljon & Longhurst, 2010), and in positively changing their attitudes towards health (Bonnema et al, 2020). In a study carried out by West and Shores (2014) to investigate the effects of the BB PA videos on the PA level of seventh-and eighth-grade students, there was an increase in the duration of student participation in moderate to vigorous activities.…”
Section: Discussionmentioning
confidence: 99%
“…Physical inactivity represent a major health burden, comparable to obesity and smoking, contributing to more than 5.3 million deaths worldwide [ 1 , 62 ]. In fact, physical inactivity is a key factor in the increase of fat storage and adiposity [ 63 , 64 ], so practicing physical activity and combating sedentariness are known as promising strategies for preventing childhood obesity [ 65 , 66 ].…”
Section: Exergames In Childhood Obesitymentioning
confidence: 99%
“…In fact, physical inactivity is a key factor in the increase of fat storage and adiposity [ 63 , 64 ], so practicing physical activity and combating sedentariness are known as promising strategies for preventing childhood obesity [ 65 , 66 ]. Globally, children and young people are becoming less active [ 1 , 67 ] and increasing their time spent in sedentary activities, such as watching television and playing videogames. The recommended daily physical activity levels for children are at least 1 h of moderate-to-vigorous-intensity physical activity [ 63 , 68 ] and less than 2 h of time spent on the screen [ 63 , 69 ].…”
Section: Exergames In Childhood Obesitymentioning
confidence: 99%
See 2 more Smart Citations